Carbon balance analysis of sewage sludge biochar-to-soil system. (15th July 2022) - Sun, Hao; Luo, Lei; Wang, Dan; Liu, Weina; Lan, Yushun; Yang, Tianxue; Gai, Chao; Liu, Zhengang
Abstract: Converting sewage sludge (SS) into biochar via pyrolysis is proposed as a prospective strategy for recycling nutrients and reducing environmental risks. Yet, from the perspective of carbon (C) balance the viability of pyrolyzing SS still remains unclear. Here we quantified the C footprint of the whole process from raw SS pyrolysis to final disposal of SS-derived biochar (SSB) using life cycle assessment based on a 20-tonne industrial pyrolysis furnace and field experiments. Results indicated that about 0.101 tonnes of direct CO2 equivalent (CO2e ) (from N-containing organic compounds in SS) plus 1.506 tonnes of indirect CO2e (from energy consumption and dewatering agents) were emitted for each tonne of dry SS treated during its dewatering and pyrolysis processes, and at least 0.252 tonnes of CO2e were sequestered as stable C in SSB, depending on the final application route of SSB. In contrast, the net C emissions from traditional SS treatments amounted to at least 2.432 tonnes of CO2e per tonne of dry SS under the similar scenarios. Converting SS into SSB thus showed great advantages in C balance over the traditional treatments of SS. Sensitivity analyses indicated that the moisture and C contents of SS and the usage of dewatering agents were the key factors affecting C balance in the SSB-to-soil system. These findings highlight the C sequestration potential of pyrolysis and provide important support for the optimization and management of SS treatment. Graphical abstract: Image 1 Highlights: Carbon balance in the whole life cycle of sewage sludge biochar (SSB) was assessed. Pyrolysis has great advantages in C balance over traditional sewage sludge treatments. Key factors affecting carbon balance for SSB were discussed using sensitivity analysis. Sewage sludge dewatering process constitutes the largest C emissions in the system.